DECONSTRUCTING ISLAMIC CYBERCULTURE: MITIGATING INFERIORITY AND CANCEL CULTURE IN VIRTUAL SPACE - Dalimunthe, Maulana Andinata; Syam, Abdi Mubarak; Suhendar, Aris; Al-Mujtahid, Nazil Mumtaz (OPINI: Journal of Communication and Social Science, 2024)
This article examines how Islamic Cyber Culture can reduce feelings of inferiority and the spread of cancel culture in virtual spaces. In Indonesia, cancel culture has increasingly affected individuals through online rejection and public petitions, while legally remaining largely unregulated. Psychologically, this phenomenon is often rooted in inferiority feelings that encourage destructive digital behavior. Using a qualitative case study approach, the study analyzes relevant cases and literature through content analysis. The findings identify four Qur’anic components of Islamic Cyber Culture: justice and equality, ethical speech and interaction, the importance of knowledge and reflection, and avoiding slander and backbiting (fitnah and ghibah). The study also highlights five urgent challenges in Indonesia: social pressure and unrealistic expectations, rapid judgment and cancellation, self-censorship, polarization and weak dialogue, and technology-driven character assassination. These challenges can be minimized by reinforcing Islamic Cyber Culture through positive narratives, digital ethics awareness, and public education, ultimately fostering a more inclusive and wise online environment.